Intrathyroidal thymic carcinoma initially suspected as a parathyroid tumor: a case report and literature review - Huang, Shunyi; Liu, Cenwen; Zeng, Xueying; Huang, Zihan; Lin, Feng; Chen, Yongyuan; Zhuo, Guanxiang; Mei, Yunyun; Guan, Qing (Frontiers in Oncology, 2025)
Intrathyroidal thymic carcinoma (ITTC) is a rare malignant tumor that presents significant diagnostic and therapeutic challenges. Herein, we present the case of a 35-year-old woman with a right neck mass initially suspected to originate from the parathyroid but ultimately diagnosed as ITTC. This case illustrates the non-specific clinical manifestations of ITTC, the associated diagnostic difficulties, and emphasizes the essential role of pathological examination in diagnosis and guiding management.